Exploring Implicit Moral Message in the Song "Que Sera- Sera " By Dorys - Yuli Rohmiyati; Davin Pratama; Jihan Camila (EDUJ : English Education Journal, 2023)
The song is one of the ways that language is used in social interaction. The lyrics of a song can be used by the writer to communicate various thoughts and concepts. People can find the song's message simply by listening to the lyrics. But many people or listeners don't understand the meaning and moral message of songs. They just enjoy the lyric of a song without knowing the meaning or message. The purpose of this research is to examine implicit moral message and significance behind the well-known song "Que Sera, Sera (Whatever Will Be, Will Be)". The song, which was famously performed by Doris Day and was written by Jay Livingston and Ray Evans, offers a philosophical viewpoint on accepting fate and life's uncertainties. The research used qualitative techniques, and the results showed that some moral messages, they are acceptance, resilience, living in the present, flexibility, gratitude and contentment, and personal reponsibility. Wish after knowing the moral message, people can promote a more purposeful and rewarding way of life